To teach modal logic : an opinionated survey - Urtubey, Luis Adrián (2015)
Fil: Urtubey, Luis Adrián. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Escuela de Filosofía; Argentina.